2011
DOI: 10.1017/s1478951511000034
|View full text |Cite
|
Sign up to set email alerts
|

Developing the social distress scale for head and neck cancer outpatients in Japan

Abstract: Results demonstrated preliminary reliability and validity of the social distress scale. This scale may extend social adjustment research by revealing its determinants and effects for head and neck cancer with facial disfigurement in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Cancer patients are often reluctant to discuss these issues with their healthcare team, so more effective screening scales [ 22 , 23 ], information, education [ 24 ] and care are needed [ 11 ]. Previous studies showed that social support and self-efficacy mediate the relationship between social distress and emotional distress in head and neck cancer patients with disfigurements [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients are often reluctant to discuss these issues with their healthcare team, so more effective screening scales [ 22 , 23 ], information, education [ 24 ] and care are needed [ 11 ]. Previous studies showed that social support and self-efficacy mediate the relationship between social distress and emotional distress in head and neck cancer patients with disfigurements [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…43 One of the vital concern reported by HNC patients is dis gurement. 44 The leading di culties lie within the area of social interaction, with people being subjected to unwanted intrusions such as staring or comments. 45 Phlegm, dry mouth, halitosis, need to spit and clear the throat are often associated with HNC.…”
Section: Discussionmentioning
confidence: 99%
“…Attitudinal items might be more likely to be somewhat affected by a patient's mood when questions were asked. Further, participants who underwent surgery were more likely to feel social distress, whereas neither the experience of chemotherapy nor radiotherapy was significantly associated with social distress (Deno et al, 2011). In other words, there may be some effect from differences in treatment.…”
Section: Discussionmentioning
confidence: 99%